Are Routines "Really" an Organizational Concept? Maybe Not for Management Accounting! - Quinn, Martin (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2017)
Since the publication of Burns and Scapens’ (2000) work which draws on the concepts of rules and routines (see also Scapens, 1994), many management accounting scholars have followed their lead. Rules and routines have been adopted, adapted and clarified in many management accounting studies since then – see for example, Oliveira and Quinn (2015); ter Bogt and Scapens, 2014; Quinn, 2014; Quinn and Jackson 2014, Bertz and Quinn, 2014; Quinn, 2011; Lukka, 2007; Ribeiro and Scapens, 2006; Spraakman, 2006; Hassan, 2005; Siti-Nabiha and Scapens, 2005; Dillard et al., 2004; Soin et al., 2002). This paper focuses on routines in particular, and how the term is potentially in need of some refined understanding in its application to studies of management accounting. In essence this paper is a monograph of a personal “routine inspired” research journey of the past decade. During this time, not only have management accounting researchers adopted routines as a conceptual tool to help empirically interpret change and stability, but our understanding of routines has been greatly assisted by organizational scholars (see for example, Pentland, 2011). While studies such as those noted above are well researched pieces of work and have advanced management accounting knowledge considerably, I have always been “bugged” by the notion of routines as an organizational concept. Early works by, for example Stene (1940) and March and Simon (1958) are quite clear in defining routines as an organization-level concept. The organizational literature similarly refers to “organizational routines”; institutional literature mentions routines as a component of institutions (which are often equated to organizations); and, structuration literature, while placing less emphasis on routines, associates its concepts with larger entities such as organizations and networks. Thus, perhaps “by default”, when we theorise on routines we associate the concept with organizations, and associate the similar concept of habit with individuals. Utilising a definition of routines put forward by Pentland (2011), this paper explores the notion that, potentially in management accounting, we can use the strong and well-grounded literature on organizational routines to study accounting practices that are not necessarily “organizational”. In particular, certain accounting concepts and technological developments are highlighted as factors which may allow us to apply routines in what extant theory might regard as “non-organizational” situations. It is argued that the extension of routines-based research to such situations opens up many opportunities for researchers in, for example, small businesses. Such businesses are often the source of many innovative commercial ideas, but sadly are frequently side-lined to “sector-specific” journals. And, as larger organizations were at one time small, we may also gain valuable insights into these too.